Title – Key Element of Text Information Structure: Array - Oleinikova, Galina (Journal of Danubian Studies and Research, 2020)
The study of the title of a literary text as a key element of the information structure of the text is inextricably linked with the problems of the status of the title of the text, its position in a text, the functional specifics of the titles of literary texts and the definition of a subtext. Active study of these issues began in the XXth century, when the text began to be considered by domestic and foreign scholars (I.V. Arnold, N.D. Arutyunova, V.A. Kukharenko, Y.M. Lotman, P. Reeker, etc.). From the point of the theory of its interpretation and also after the appearance of the theory of text information structure by I.R. Galperin. Different views of researchers on the definition of the phenomenon of a subtext, the status of the title of a text, the functional specificity of the titles of texts of different genres indicate the complexity and interdependence of all above issues. The scientific significance and relevance of the issues of understanding and interpretation of the title of the work of art as a key element of the text information structure remains debatable these days.